A case of electric injury with exposed neck vessels and scapula treated with flaps - Vijay Bhatia; Archana Thakur; Sruja Narola; Manisha Singh; Rahul Kaushik; Deepanjali Kalra (Wolters Kluwer Medknow Publications, 2022)
In modern times, the use of electricity has increased many times and so has the incidence of high-voltage electrical injuries. The incidence of high-voltage electrical injuries is much higher in developing countries when compared to developed countries, lack of proper transmission systems being the cause. Electric burn injuries lead to debilitating morbidity to the affected patients and are often deadly. In such cases with exposed vessels in the neck, major flaps such as the deltopectoral flap or forehead flap or free flaps increase the hospital stay or two-staged procedures and hence increase the morbidity of such patients. Here, we present a case of a young male patient who sustained an electric injury to his foot, neck, and shoulder, which was managed with the platysma flap and parascapular flap with no donor site morbidity.